SISTEM MONITORING PENJADWALAN MAINTENANCE PERALATAN KONSTRUKSI DI PT. PRIMA KONSTRUKSI UTAMA - Widyawati Widyawati; Irfan Fadillah (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
PT Prima Konstruksi Utama is an experienced company in the construction services sector. The equipment used by the company faces various maintenance challenges. Equipment breakdowns during construction projects can cause delays and missed deadlines. Without an effective monitoring system, there is a risk of overlapping or neglect in equipment maintenance, negatively impacting productivity and costs. Therefore, a maintenance scheduling monitoring system with priority algorithms is needed to ensure all equipment is in good condition and ready for use when required, prioritizing the most important maintenance tasks. This maintenance scheduling monitoring system is designed using the Laravel framework, Bootstrap, and MySQL Database Management System (DBMS). The development of this web system employs the waterfall method and Unified Modeling Language (UML). This system facilitates and accelerates the maintenance process by providing information on repair and maintenance schedules, simplifying the repair request process from the person in charge to the maintenance manager, and assisting in the creation of repair and maintenance reports.